Sex Differences in the Relationship of Dietary Fatty Acids to Cognitive Measures in American Children - Lassek, Will; Gaulin, Steven (Frontiers in Evolutionary Neuroscience, 2011)
Because the first neurons evolved in an environment high in the n-3 (omega-3) fatty acid docosahexaenoic acid (DHA), this fatty acid became a major component of neural structure and function and makes up 10% of the dry weight of the human brain. Since n-3 fatty acids must come from the diet, this suggests a possible positive role for dietary n-3 fatty acids in cognition and a possible negative role for n-6 fatty acids, which compete with n-3 for access to critical enzymes. Because human females must provide DHA for the growth of the unusually large brains of their offspring from maternal fat stored during childhood, their need for DHA is especially great. We used stepwise regression to determine whether particular dietary fatty acids and other nutrients were related to cognitive performance in over 4000 American children aged 6 to 16 from the Third National Health and Nutrition Examination Survey (NHANES III); a variety of possible biological, social and environmental risk factors were statistically controlled. In this context the only dietary factors related to cognitive performance were n-3 and n-6 fatty acids. Dietary n-3 fatty acids were positively related to cognitive test scores in male and female children, while n-6 showed the reverse relationship, significantly so in females. In female children the positive effects of n-3 intake were twice as strong as in males and exceeded the negative effects of lead exposure. This suggests that increasing dietary intake of n-3 and decreasing n-6 fatty acids may have cognitive benefits in children, especially in females.